A pan-cancer analysis reveals role of clusterin (CLU) in carcinogenesis and prognosis of human tumors - Fu, Yizhe; Du, Qiao; Cui, Tiehan; Lu, Yuying; Niu, Guangliang (Frontiers in Genetics, 2023)
Clusterin (CLU) is a chaperone‐like protein that was demonstrated to have a direct relationship with cancer occurrence, progression, or metastasis. CLU was identified as down-regulated in tumor tissues using three datasets of tongue squamous carcinoma from Gene expression omnibus (GEO). We further retrieved datasets from the cancer genome atlas (TCGA) and GEO to undertake a thorough investigation of the carcinogenic consequences for CLU. Our findings revealed that the decreased CLU expression in malignancies was connected with a worse overall survival prognosis in individuals with multiple tumors; CLU gene deep deletions were found in almost all malignancies and were connected to most cancer patient’s prognosis; CLU DNA methylation level was dependent on tumor types; CLU expression was also linked to the invasion of cancer-associated CD8+ T-cells and fibroblasts in numerous cancer forms. Moreover, pathway enrichment analysis exposed that CLU primarily regulates biological processes such as cholesterol metabolism, phospholipid binding, and protein-lipid complex formation. Overall, our pan-cancer research suggests that CLU expression level is linked to tumor carcinogenesis and prognosis, which contributes to understanding the probable mechanism of CLU in tumorigenesis as well as its clinical prognostic significance.